Studi Pemanfaatan Tanaman Kelor (Moringa oleifera) Sebagai Pengobatan Tradisional di Kampung Cibeas Desa Cintaraja Kecamatan Singaparna Kabupaten Tasikmalaya - Rifa Musyaropah; Tri Cahyanto (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Moringa oleifera plants as traditional medicine used by the people of Cibeas Village, Cintaraja Village, Singaparna District, Tasikmalaya Regency. This study aims to determine the use of moringa plants as traditional medicine. The method used is descriptive qualitative and quantitative with data collection techniques through observation, semi-structured interviews, and snowball sampling. Data analysis was carried out by calculating the utility value (Use Value/UV), informant context factors (Informant Consensus Factor/ICF), and relative citation frequency (Relative Frequency of Citation/RFC). The results showed that moringa plants are used to treat 12 types of diseases, with the highest utilization for lowering hypertension (UV = 0.296). The leaves are the most frequently used part (ICF = 0.952).